Slovak Republic : 2011 Article IV Consultation-Staff Report; Informational Annex; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Slovak economy showed recovery from sharp recession. Executive Directors suggested that restoring fiscal sustainability and removing unemployment while maintaining external competitiveness within the monetary union should be given priority. The fiscal consolidation strategy could be facilitated by adopting real expenditure growth with deficit targets and expenditure policy priorities, including reforming health care and pensions. However, public procurement and absorption of EU funds are important for enhancing the business environment and strengthening public sector governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet